Retraction Note: Reduction of carbon dioxide to oxalate by a binuclear copper complex - Uttam R. Pokharel (Nature Portfolio, 2021)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1038/s41467-021-21951-5